ROZIA KARIMOVA: THE PATH TO GREATNESS AND INSPIRATION - Safarovna , Safarova Zilola (Journal of Higher Education and Academic Advancement, 2024)
Objective: This article examines the life and contributions of Rozia Karimova, a pivotal figure in the preservation and development of Uzbek folk dance, highlighting her heroic efforts during the Second World War and her subsequent work in choreographic scholarship. Methods: The research employs a combination of validity, systematicity, comparative analysis, and synthesis to evaluate Karimova's impact on Uzbek dance. Statistical analysis is also utilized to assess the influence of her pedagogical works. Results: Rozia Karimova pioneered the documentation and systematization of Uzbek folk dance, creating the first comprehensive textbooks on regional dance styles, including Fergana, Khorezm, and Bukhara. Her works, such as Fergana Dance (1973), Khorezm Dance (1975), and Bukhara Dance (1977), became foundational texts for dancers and choreographers. Karimova’s contributions were recognized with prestigious awards, including the title of People’s Artist of Uzbekistan. Novelty: The article underscores Karimova’s unique role in transforming Uzbek folk dance from an oral tradition into a formalized, scholarly discipline, establishing her as a pioneering figure in the field of choreographic studies.